Wpływ osadu komunalnego i kompostu z odpadów zieleni na jakość czterech mieszanek trawnikowych = Effect of municipal sewage sludge and compost from green areas wastes on the quality of lawn compound - Kitczak, Teodor; Czyż, Henryk (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Two-factor experiment was assumed in spring 2004 in the Split-splot system on plots with an area of 6 m2 in three replications. Sewage sludge and compost applied to soil in autumn in amound of 20 t ha-1, for the winter plowing. To evaluate the fertilizer value of sewage sludge and compost used four lawn mixture: Festuca arundinacea, Festuca rubra, Lolium perenne and Poa pratensis.
Keywords: grunt rodzimy; podłoże z kompostem; podłoże z osadem; mieszanki traw; zadarnienie; grass mixtures; ground native; sodding, soil of compost; soilof supplement